Cations Do Not Alter the Membrane Structure of POPC—A Lipid With an Intermediate Area - Kurakin, Sergei; Ivankov, Oleksandr; Skoi, Vadim; Kuklin, Alexander; Uhríková, Daniela; Kučerka, Norbert (Frontiers in Molecular Biosciences, 2022)
Combining small angle neutron scattering (SANS), small angle X-ray scattering (SAXS), and densitometric measurements, we have studied the interactions of the divalent cations Ca2+ and Mg2+ with the lipid vesicles prepared of a mixed-chain palmitoyl-oleoyl-phosphatidylcholine (POPC) at 25oC. The structural parameters of the POPC bilayer, such as the bilayer thickness, lateral area, and volume per lipid, displayed no changes upon the ion addition at concentrations up to 30 mM and minor changes at > 30 mM Ca2+ and Mg2+, while some decrease in the vesicle radius was observed over the entire concentration range studied. This examination allows us to validate the concept of lipid-ion interactions governed by the area per lipid suggested previously and to propose the mixed mode of those interactions that emerge in the POPC vesicles. We speculate that the average area per POPC lipid that corresponds to the cutoff length of lipid-ion interactions, generates an equal but opposite impact of ion bridges and separate lipid-ion pairs. As a result of the dynamic equilibrium, the overall structural properties of bilayers are not affected. As the molecular mechanism proposed is affected by the structural properties of particular lipid, it might help us to understand the fundamentals of processes occurring in complex multicomponent membrane systems.